Financial controlling status and potential in medium-sized enterprises of Tuzla Canton, Bosnia and Herzegovina - Emira Kozarević; Amir Mujezinović (Economic Review: Journal of Economics and Business, 2020)
The paper focuses on financial controlling in the role of improving business performances of medium-sized enterprises in the Tuzla Canton, Bosnia and Herzegovina, active in manufacturing, trade, transport and storage, construction, etc. All the processes accompanying these activities are significantly faster and do not run in a classical way, which is why the management system nowadays requires that information requested within plan, analysis, and control run simultaneously. It is emphasized that financial controlling is important as it provides the necessary coordination and outgoing information for the management of a medium-sized enterprise. The authors also researched and identified unique common indicators used for determining and establishing financial controlling in medium-sized enterprises in the Tuzla Canton, analyzed the obtained results, and identified mutual dependence of financial controlling and performances of medium-sized enterprises. The conducted research points to the basic conclusion that the function (department) of financial controlling in modern organization of medium-sized enterprise is needed and has a positive effect. The authors therefore confirmed the hypothesis that financial controlling, if properly implemented in practice at the level of medium-sized enterprise, gives efficient results.
Keywords: G30; G39; 330; financial controlling; medium-sized enterprises; performances; Tuzla Canton; Bosnia and Herzegovina